2019
DOI: 10.1371/journal.pbio.3000553
|View full text |Cite
|
Sign up to set email alerts
|

Image-based analysis of living mammalian cells using label-free 3D refractive index maps reveals new organelle dynamics and dry mass flux

Abstract: Holo-tomographic microscopy (HTM) is a label-free microscopy method reporting the fine changes of a cell’s refractive indices (RIs) in three dimensions at high spatial and temporal resolution. By combining HTM with epifluorescence, we demonstrate that mammalian cellular organelles such as lipid droplets (LDs) and mitochondria show specific RI 3D patterns. To go further, we developed a computer-vision strategy using FIJI, CellProfiler3 (CP3), and custom code that allows us to use the fine images obtained by HTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 64 publications
6
87
0
Order By: Relevance
“…The increase in dry mass density at the leading edge was associated with membrane protrusion or with structures resembling peripheral ruffles [ 63 ]. Hence, ours and other recent reports [ 62 , 68 , 69 ] stress the potential of label-free non-invasive microscopy in the identification of novel aspects of cell behavior and physiology.…”
Section: Discussionsupporting
confidence: 57%
“…The increase in dry mass density at the leading edge was associated with membrane protrusion or with structures resembling peripheral ruffles [ 63 ]. Hence, ours and other recent reports [ 62 , 68 , 69 ] stress the potential of label-free non-invasive microscopy in the identification of novel aspects of cell behavior and physiology.…”
Section: Discussionsupporting
confidence: 57%
“…While direct observation of NL fluxes within the ER is technically challenging, rapid advances in imaging and probe technologies (Valm et al, 2017;Adhikari et al, 2019) are likely to facilitate this in the near future. Findings from a recent study, employing elegant imaging techniques (holo-tomographic microscopy), support the notion of a fluid connection of LDs through the ER (Sandoz et al, 2019). It was found that LD growth in a given cell during fatty acid administration was highly synchronous, with both shrinking and growing of LDs happening in concert, as if sharing a common pool of lipid precursors.Furthermore, upon initial LD assembly, preexisting LDs actually initially slightly shrunk in size at the same time as numerous new LDs emerged.…”
Section: The Er-ld Network As a Joint Systemmentioning
confidence: 78%
“…Increased spatial resolution or prolonged exposure would lead to the distribution of the LE/LY signal across an even larger field of view and the ultimate disappearance of the structure into the background noise. Similarly, because ER tubules and junctions also undergo rapid motions in live cells 41 , they have never been observed by any ODT microscopes in live cells previously, and such an observation has even been deemed to be impossible 10 . Therefore, the spatial resolution must be matched with the corresponding temporal resolution to enable the maximal resolution achievable in live-cell ODT imaging, which has been overlooked in previous designs 6,9,13 .…”
Section: Discussionmentioning
confidence: 99%
“…S8), we used Wiener filtering (Eq. (10) in Supplementary Note 3) to reconstruct the 3D distribution of the RIs within the cell.…”
Section: Experimental Implementation and Image Reconstruction Of Sr-factmentioning
confidence: 99%
See 1 more Smart Citation